The Diversity Rationale in Higher Education: An Overview of the Contemporary Legal Context - Aguirre, Adalberto (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. Court decisions that have challenged the context for diversity and affirmative action interventions in relation to higher education are examined. A contextual framework is outlined to inform the exploration of issues of affirmative action—a social policy initiative designed to halt discriminatory practices by allowing the consideration of race, ethnicity, sex, or national origin in the selection process—and diversity within higher education.